Evaluation of the influence of texture and microstructure of titanium substrates on TiO2 anodic coatings at 60 V - Vera, María Laura (2017)
Fil: Vera, María Laura. Consejo Nacional de Investigaciones Científicas y Técnicas. Centro Científico Tecnológico (Nordeste). Instituto de Materiales de Misiones; Argentina.